Polymer Macro- and Micro-Gel Beads: Fundamentals and Applications - Nussinovitch, Amos. (Springer New York : Imprint: Springer, 2010)
Although the use of water-soluble polymer beads is on the rise in many fields, the literature offers only scattered chapters in a handful of books on the topic. Polymer Macro- and Micro-Gel Beads: Fundamentals and Applications fills this void. It covers both the properties and traditional and novel applications of polymeric beads, making it a crucial addition to the literature. This book describes numerous methods of bead production, as well as the techniques used to modify them and to estimate their physical and chemical properties. A full description of past and present developments and applications of beads in the fields of agriculture, biotechnology, environmental studies, medicine, pharmacology, and food are presented. Amos Nussinovitch is a Professor of Food Science and Technology at The Robert H. Smith Faculty of Agriculture, Food and Environment, The Hebrew University of Jerusalem. He is an internationally recognized expert on hydrocolloid applications and works in the areas of structure and texture of wet and dry beads, liquid-core capsules, different polymeric beads for water denitrification and beads as part of novel cellular solids, among many other applications.